MENINGKATKAN KEPUASAN PENGUNJUNG WISATAWAN LANSIA DI TMII INDONESIA - Akhirson, Armaini; Br. Pareangin-angin, Rosliyana; Apriyanti, Rehulina (Universitas Gunadarma, 2023)
This study aims to determine the effect of facilities partially on the satisfaction of TMII elderly visitors, the effect of partial accessibility on the satisfaction of elderly visitors to TMII and the effect of facilities and accessibility simultaneously on visitor satisfaction of elderly visitors to TMII. This research method uses a questionnaire instrument distributed to 100 respondents. The sampling method in this study was purposive sampling technique. The data collected was then processed using the SPSS 22 application with the analysis tools of the Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, Hypothesis Test, and Determination Coefficient Test. The results showed that the facility variable partially has a positive and significant effect on the satisfaction of elderly visitors to Taman Mini Indonesia Indah. The accessibility variable partially has a positive and significant effect on the satisfaction of elderly visitors to Taman Mini Indonesia Indah. Facilities and accessibility simultaneously affect the satisfaction of elderly visitors to Taman Mini Indonesia Indah.